Neck Rejuvenation—Anatomy and Clinical Correlation - Huettner, Franziska; Vasconez, Luis O.; de la Torre, Jorge I. (Facial Plastic Surgery, 2012)
The restoration of the aesthetic contour of the neck is a challenging but important component of facial rejuvenation. Numerous techniques have been developed to improve the aesthetic outcome. We plan to give an overview of anatomic principles and their clinical correlation.
Keywords: neck; rejuvenation; techniques